The characterization of banana blossom peel and floret as an adsorbent for the removal of manganese in groundwater - Omar, Suhair; Mohd Yusoff, Nor Syahidah; Muhamad, Mimi Suliza; Hamidon, Nuramidah; Abdul Hamid, Nor Hazren; Harun, Hasnida; Mohamed Sunar, Norshuhaila; Ali, Roslinda (Trans Tech Publications, 2020)
Manganese (Mn) is one of the most serious pollutants that have negative effects on the ecosystem and water supply. The water industry faces major challenges in its treatment for contaminant and in developing an alternative product with low cost. Among various adsorbents, agriculture waste is preferred due to its biodegradability and availability. The removal of manganese (Mn) from groundwater was investigated using two different adsorbents which are banana blossom peel and floret. SEM analysis shows the formation of microporous structure for both banana blossom peels and floret while FTIR analysis confirms the functional group of strong hydroxyl group that responsible for the adsorption process. The water quality index for the groundwater sample was classified into class III which required extensive treatment. Batch adsorption experiments revealed that both adsorbents had maximum removal efficiency using 0.5 g adsorbent dosage. The banana blossom peel reduces Mn to 0.10 mg/L with 81.1% removal, while the banana blossom floret reduces Mn concentration to 0.12 mg/L with 77.7% removal.